Axion couplings in gauged U(1)′ extensions of the Standard Model - Alexey Kivel; Julien Laux; Felix Yu (Journal of High Energy Physics, 2023)
Abstract We explore the effective theory of an axion in a gauged baryon number symmetry extension of the Standard Model (SM), where the axion is realized from a Dine-Fischler-Srednicki-Zhitnitsky (DFSZ) model construction. Integrating out the anomalons realizes a pattern of effective Wilson coefficients reflecting the factorization between the anomalous Peccei-Quinn and gauged baryon number symmetries. We construct and analyze the chiral transformation invariance of the axion effective theory, accounting for possible flavor-violating axion couplings. We calculate and study the unique phenomenology of the axion and Z′ boson, and we present the current collider limits on these particles in the m Z ′ g B $$ \left\{{m}_{Z^{′ }},{g}_B\right\} $$ , {m a , G aγγ }, and m a f a − 1 $$ \left\{{m}_a,{f}_a^{-1}\right\} $$ planes.